2006
DOI: 10.1207/s15374424jccp3501_1
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Research-Practice Gap: Factors Affecting Adoption and Implementation of a Children's Mental Health Program

Abstract: Despite the availability of effective interventions, they are not widely used in community mental health centers. This study examined the adoption and implementation of The Arson Prevention Program for Children (TAPP-C), a program for juvenile firesetters developed at a teaching hospital and disseminated to community settings. Questionnaire data from mental health professionals were used to evaluate the roles of adopter, innovation, and dissemination characteristics in TAPP-C adoption and implementation. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 75 publications
1
64
0
Order By: Relevance
“…Change at multiple levels including that of the practitioner, team, organization, and larger system is necessary to effect large-scale change in treatment delivery. Evidence-based treatments need to be perceived by community-based mental health professionals as easy and compatible with existing services (12). Similarly, the intervention's fit with an organization's current service delivery structure, mission, interests, and resources influences its ease of implementation (13).…”
Section: Discussionmentioning
confidence: 99%
“…Change at multiple levels including that of the practitioner, team, organization, and larger system is necessary to effect large-scale change in treatment delivery. Evidence-based treatments need to be perceived by community-based mental health professionals as easy and compatible with existing services (12). Similarly, the intervention's fit with an organization's current service delivery structure, mission, interests, and resources influences its ease of implementation (13).…”
Section: Discussionmentioning
confidence: 99%
“…Such studies offer useful directions for future research. For example, a regression analysis indicated that training and providers' sense of self-efficacy emerged as significant predictors of the implementation of an arson prevention program for children, whereas technical assistance and intervention complexity did not (Henderson et al 2006). Kallestad and Olweus (2003) studied the implementation of school-wide anti-bulling programs in Norway.…”
Section: Relationships Among Factorsmentioning
confidence: 99%
“…Despite a general awareness of the problem (Henderson et al 2006), researchers in children's mental health have produced no research on the quality chasm-that is, no formally documented studies of the extent of or reasons for the gap nor of the degree to which the gap varies across disorders, intervention types, provider disciplines, clinical populations, or environmental contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, studies have identified a variety of reasons for translation difficulties (e.g., Henderson et al 2006;Fixsen et al 2005), including (1). These include intervention characteristics (e.g., cost, time demands, level of staff expertise required, difficulties learning the intervention, lack of fit between the intervention and end users' needs, failure to consider how to make the intervention self-sustaining, difficulties customizing the intervention to real-world practice settings, intervention specificity to a particular setting, differences between intervention demands of a pharmacologic versus a psychotherapeutic intervention, etc.)…”
Section: Introductionmentioning
confidence: 99%